Supraventricular Tachycardia Triggered after Central Venous Catheter Insertion - Alfredo Aurélio Marinho Rosa Filho; Caio Conde Merten; Dandara Dias Gomes da Cunha; Briane Alcântara Vieira Pasini; Carlos Romério Costa Ferro (Journal of Cardiac Arrhythmias, 2022)
Central venous access is an established procedure in clinical practice. A misplaced central venous catheter can induce supraventricular and ventricular arrhythmias. We describe the case of a 60-year-old female patient with a recent diagnosis of multiple myeloma hospitalized for chemotherapy. The patient had an episode of supraventricular tachycardia after installing a central venous catheter. The electrocardiogram of the case in question showed a RP’ interval of 60 ms, corroborating the nodal reentry mechanism with the probable mechanism of tachycardia. The present report draws attention to the need for caution during the installation of these central venous catheters.